Integrasi Teori Behavior dalam Konseling Individu dan Kelompok - -, Tri Wulandari; Dina Hajja Ristianti; Beni Azwar; Sumarto (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2024)
The integration of behavior theory in individual and group counseling has emerged as a pertinent topic in psychology and counseling. Stemming from the works of pioneers like John B. Watson and B.F. Skinner, behavior theory emphasizes observable behavior change through environmental understanding and modification. This paper explores its application in counseling, examining benefits, challenges, and effective techniques such as reinforcement, exposure therapy, modeling, and behavioral activation. While offering structured, data-driven approaches, integration faces challenges like neglecting internal client factors and therapeutic rapport. Nevertheless, its structured framework facilitates goal setting, intervention, and evaluation, promoting positive behavior change and psychological well-being